The Role of Guidance Personnel in the Prevention of Child Abuse - Burns, George E.; Barber, Paula (Canadian Journal of Counselling and Psychotherapy, 2011)
The general problem which this paper addresses is the relational clarification of child abuse prevention roles. The roles are in relation to jurisdictions differentially involved in policy development, adoption, or implementation processes. Combined, the jurisdictions comprise an internally consistent interactive social system for improving the implementation of child abuse prevention practices in educational systems and school settings. The article presents profiles for the Ministry of Education, school boards, school principals, classroom teachers, and discusses in detail the role of guidance personnel. The paper illustrates that the role profiles can be developed in the context of a general framework and its organizing constructs. The paper reveals that the roles of guidance personnel are integral to an overall system of coordinated action.